Cyclic voltammetry characterization analysis on the cu/flame retardant 4 fabricated biosensor - Irni Hamiza Hamzah; Azman Ab Malik; Aida Zulia Zulhanip; Zainal Hisham Che Soh; Alhan Farhanah Abd Rahim (Institute of Advanced Engineering and Science, 2020)
Silicon, glass and ceramic are commonly base substrate used in DNA biosensor fabrication due to its biocompatible, expensive, hard and brittle. However due to the difficulty for drilling and dicing, these materials required expensive equipments and complex methodology of fabrication. Large gap of thermal expansion coefficient (TEC) between silicon/glass and film caused microcracks. Hence, the aim of this work is to investigate the suitability and the application of a non-biocompatible material, flame retardant 4 (FR4) as a base substrate for a label free DNA biosensor. Cyclic voltammetry (CV) reversible method has been implemented to test the fabricated Cu/Au on the FR4. It is found that the fabrication of Au has been made possible by the used of oxide-free Cu as an adhesion layer on the FR4 substrate. The area size of counter electrode (CE), working electrode (WE) and reference electrode (RE) are found to be 6.25 mm2, 0.581 mm2 and 1.04 mm2, respectively, in order to achieve the unity reversible redox relationship and to ensure the sensor’s reliability for 10 mM K3Fe(CN)6 solution in 0.1 M KCl. Thus it can be concluded that the proposed FR4-based substrate fulfilled the CV reversible process characterization.